Maternal Nicotine Exposure During Gestation and Lactation Period Affects Behavior and Hippocampal Neurogenesis in Mouse Offspring - Liu, Fei; Tao, Xinrong; Pang, Gang; Wu, Diqing; Hu, Yuting; Xue, Song; Liu, Jing; Li, Bing; Zhou, Li; Liu, Qiang; Zhang, Yong-Mei (Frontiers in Pharmacology, 2020)
Cigarette smoking or nicotine exposure during pregnancy is associated with numerous obstetrical, fetal, and developmental complications, as well as an increased risk of adverse health consequences in the adult offspring. In this study, we examined the effects of maternal nicotine exposure during perinatal and lactation stages on behavioral performance and hippocampal neurogenesis in the adolescent stage of offspring mice. Female C57BL/ mice received nicotine in drinking water (200 μg/mL nicotine) or vehicle (1% saccharin) starting from 2 weeks pre-mating until the offspring were weaned on postnatal day 20. Experiments started on postnatal day 35. Female offspring with maternal nicotine exposure presented an increase in anxiety-like behavior in an open-field test. BrdU assay revealed that nicotine offspring presented an increase in cell proliferation in hippocampal dentate gyrus, but the number of BrdU+ cells was decreased in one week and further decreased in three weeks. The occurrence of disarray of DCX+ cells increased in both male and female nicotine offspring. The density of microglial marker protein Iba1 was significantly increased in the nicotine offspring. Furthermore, the expression of microglia marker Iba1, the CX3CL1, CX3CR1 and downstream molecules PKA and p-ErK were significantly increased in the nicotine group. In summary, maternal nicotine exposure affects both hippocampal neurogenesis and microglial activity in the adolescent offspring.